Metamorphosing waste as a resource: Scaling waste management by ecomodernist means. Issue 98 (January 2019) - Levidow, Les; Raman, Sujatha
Abstract: Informed by the European Union's waste hierarchy, UK policy has normatively shifted the ontological status of waste from matter out of place to a resource for which uses must be found in order to achieve environmental goals of decarbonisation and waste reduction. Technologies linking waste-management with renewable energy have been supported within an ecomodernist framework of market incentives for stimulating private-sector investment in new waste treatment technologies. Under pressure of EU targets, the UK's policy measures have had several aims: to reduce landfill disposal, increase resource recycling or reuse, expand waste-based renewable energy and thus reduce GHG emissions. As techno-market-fixes, new facilities were meant to convert waste for more beneficial uses, bring it up the hierarchy and localise its management. Consequent tensions can be illuminated by linking concepts of technology scaling and socio-material metamorphosis with critical perspectives on ecomodernism. Although the ecomodernist framework stimulated some waste-management improvements, other outcomes contradict the policy objectives of localising and converting waste for more beneficial uses. These contrary outcomes are illustrated by two technologies, anaerobic digestion (AD) and mechanical and biological treatment (MBT), each with multiple possible spatial scalings and techno-configurations. Financial instruments have most incentivised the easiest socio-material metamorphosis for lucrative returns, especially to produce energy (electricity or gas) for grid systems, suiting large operators. For more environmentally beneficial uses of waste, there have been difficulties in overcoming its recalcitrance for producing commercially viable outputs, e.g. digestate replacing chemical fertilisers, compost improving soil and 'dirty' plastics replacing virgin plastics. Techno-configurations and material flows have been scaled towards global goods, distant from the feedstock source. Through the ecomodernist framework, the state's responsibility for such outcomes has been blurred with the private sector and shifted to anonymous markets.